POST- PURCHASE DISSONANCE OF CONSUMERS AND TRADERS’ RESPONSES IN KERALA - S. Krishnamoorthy and V. Ajith Prabhu
Consumers are exploited in the market and due to several reasons they are ignorant of the exploitation to which they are subjected to. The purpose of the study is to ascertain the reasons of post- purchase dissonance and whether there is any correlation between the demographic variables and post-purchase dissonance. Data were collected from 238 samples from the consumers, who have filed petitions in various forums in Kerala. Similarly, data from 205 manufacturers, traders and service providers were collected. The data collected using questionnaire were analyzed using Mean, Kruskal Wallis Test, Mann-Whitney U Test and Friedman Test. The result shows that there is a relationship between reasons for post purchase dissonance and demographic variables and it varies on the basis of location and gender of the consumers